(4-3x)(10-9x)=0

Simple and best practice solution for (4-3x)(10-9x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4-3x)(10-9x)=0 equation:



(4-3x)(10-9x)=0
We add all the numbers together, and all the variables
(-3x+4)(-9x+10)=0
We multiply parentheses ..
(+27x^2-30x-36x+40)=0
We get rid of parentheses
27x^2-30x-36x+40=0
We add all the numbers together, and all the variables
27x^2-66x+40=0
a = 27; b = -66; c = +40;
Δ = b2-4ac
Δ = -662-4·27·40
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-66)-6}{2*27}=\frac{60}{54} =1+1/9 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-66)+6}{2*27}=\frac{72}{54} =1+1/3 $

See similar equations:

| 2y-4(3y+5)=-50 | | 4x+3(2x-8)=26 | | 10+384=-9(-2-6w)-7w | | 1/4(12-3x)=-6 | | -300=-20m | | 5x+14+21=104 | | -3(k-8)(-k+5)=23 | | 12=9x+4=5x | | 13-2m=5(2m-7) | | 5(4+r)=20-5r | | 12y+-6=12 | | 2m−3=13* | | 6x-10=34-2x | | 6x+8+6=32 | | 4x–20=2x–6 | | 23-7=4y-20+5y | | -3x+33=-1/ | | 8/3x+3=7/6x-4 | | 6x+78x-17=180 | | 13q=0 | | 5(4-3x=-10 | | 12=p+2p-3 | | 0.5x+4=-16 | | 3e-30=-2e-15 | | -2x+40=60 | | (5x+3)+97=180 | | x=192/5 | | 1x2=3(x+4) | | n+9=(4)=120 | | 10/4y-12=-2 | | 5x+4=4(x-2)+12 | | 3(2d-8)=54-7d |

Equations solver categories